Subprime mortgage lending in New York City: Prevalence and performance - Ebiere Okah; James Orr (Federal Reserve Bank of New York, 2010)
Subprime mortgage lending expanded in New York City between 2004 and mid-2007, and delinquencies on these subprime loans have been rising sharply. We use a rich, loan-level data set of the city's outstanding subprime loans as of January 2009 to describe the main features of this lending and to model the performance of these loans. These subprime loans represent a smaller share of total housing units in the city than is true nationwide. In addition, they are found to be clustered in neighborhoods where average borrower credit quality is low and, unlike prime mortgage loans, where African-Americans and Hispanics constitute relatively large shares of the population. We estimate a model of the likelihood that these loans will become seriously delinquent and find a significant role for credit quality of borrowers, debt-to-income and loan-to-value ratios at the time of loan origination, and estimates of the loss of home equity.
Keywords: R10; R23; 330; New York City; subprime lending; Subprime-Hypothek; New York (NY)